2015
DOI: 10.1007/s10544-015-9983-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical performance of a low cost near infrared sensor for continuous glucose monitoring applied with subcutaneous microdialysis

Abstract: In this work we present a low cost, minimally invasive, and chip-based near infrared (NIR) sensor, combined with subcutaneous microdialysis, for continuous glucose monitoring (CGM). The sensor principle is based on difference absorption spectroscopy in the 1st overtone band known to be dominated by glucose-specific absorption features. The device comprises a multi-emitter LED and InGaAs-photodiodes, which are located on a single electronic board (non-disposable part), connected to a personal computer via Bluet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…A minimally invasive chip-based NIR CGM sensor using microdialysis of ISF has been suggested by Mohammadi et al The sensor has been used in two in vivo trials, the first on 10 DM1 patients for 30 hours (77), and the second one with six subjects for 12 hours (78). The glucose concentration range was approximately 60-350 mg/dl.…”
Section: Research Statusmentioning
confidence: 99%
“…A minimally invasive chip-based NIR CGM sensor using microdialysis of ISF has been suggested by Mohammadi et al The sensor has been used in two in vivo trials, the first on 10 DM1 patients for 30 hours (77), and the second one with six subjects for 12 hours (78). The glucose concentration range was approximately 60-350 mg/dl.…”
Section: Research Statusmentioning
confidence: 99%
“…Within continuous glucose monitoring devices, we defined a total of 7 groups based on the similarity of the devices and the manufacturer: Medtronic devices, 21 - 24 Eversense (Senseonics), 21 , 25 - 28 Dexcom devices, 21 , 23 , 29 - 36 Glucotrack (Integrity Applications), 37 , 38 an infrared sensor for subcutaneous microdialysis (Fraunhofer ICT-IMM), 39 subcutaneous monitoring systems (Biovotion), 40 and NovioSense glucose sensor (NovioSense). 41 All of the mentioned devices measured glucose levels on interstitial tissue or tears (see Figure 2 and Supplemental Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“… 20 , 57 In this study, we opted to use MARD, an indicator that evaluates variability between measurements, with a stringent cutoff point of 10% and we found that the only device that met the criteria were TensorTip Combo Glucometer 48 and the Opto-fluidic near-infrared (NIR) continuous glucose monitor. 39 Nevertheless, each of the devices had only 1 validation study, suggesting a need to conduct more studies to compare and contrast the results as the MARD is usually very variable.…”
Section: Discussionmentioning
confidence: 99%
“…In 2015, they followed up with a demonstration for establishing a non-invasive model according to Beer-Lambert's law rather than using chemometrics [95]. In the same year, Mohammadi et al reported a minimally invasive NIR CGM system using microdialysis of ISF and tested on six T1D patients [70]. molecules, such as lactate and urea (Figure 5D) [87].…”
Section: Near-infrared (Nir) Spectroscopymentioning
confidence: 99%